The Influence Of Organizational Culture And Work Motivation On Employee Performance With Satisfaction Work As Variables Mediation (Studies Case On Cv. Mdc Group Lamongan) - Lestari, Edi; Muhtarom, Abid; Yaskun, Mohammad (UNIVERSITAS PAKUAN, 2024)
Human resources are the most important element in a company because employees play an active role in every change towards a better direction. This research aims to determine the influence of organizational culture and work motivation on employee performance, as well as the influence of both through job satisfaction. Using explanatory research methods with a quantitative approach and Partial Least Square (PLS) analysis via SmartPLS software, this research involved 88 CV employee respondents. The Lamongan MDC Group was selected using proportional random sampling technique and an error rate of 10%. Data was collected through questionnaires. The research results show that organizational culture has a significant positive effect on employee performance, while work motivation has a positive but not significant effect. However, both organizational culture and work motivation have a significant effect on employee performance through job satisfaction, emphasizing the importance of paying attention to organizational culture and work motivation to improve overall employee performance.